THE FUNCTION OF COLOR IMAGES IN REVEALING THE PSYCHE OF THE LYRICAL HERO (International journal of artificial intelligence, 2025)
This article examines the artistic and aesthetic function of color imagery in expressing the emotional state of the lyrical hero. In poetry, colors serve not only as elements of the landscape but also as a means of conveying emotional and philosophical meanings. The symbolic meanings of colors and their role in creating poetic images are analyzed.